Visual Quality of Tunjungan District in Surabaya - Reza Hidayatullah; Jenny Ernawati (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
A lot of changes happened to the architecture and urban design of heritage district that influence community’s experience and responses. Tunjungan street is one of heritage district that connects northern and southern area of Surabaya. The importance of this heritage district’s location raises a crucial question about the visual quality that created,as this heritage district is one of the Surabaya city’s main face. This research measured people’s preferences on heritage district’s visual quality in Tunjungan street. Using linear-numeric semantic differential and 22 variables, and also human scale photos of the district as a stimuli. The result show that existing corridor indicates early integration in architectural style between new building and the old one, unharmonious setback, uses reflective material, and also moderate transparency level. There were three main factorsof Tunjungan district’s visual quality resulted from this research: Attractiveness, Continuity, and Movements. The most influential factor in the process of creating visual quality is Attractiveness, followed by Continuity, and Movement.Keywords: Visual quality, Heritage district, Tunjungan street, People’s preference